ANALISIS KOMPARASI PENGARUH RISIKO SISTEMATIS TERHADAP RETURN SAHAM SEKTORAL DI INDONESIA PADA MASA PERANG RUSIA-UKRAINA DAN KRISIS PROPERTI CHINA - Pradani, Amaretta Hanindya; David Kaluge (Contemporary Studies in Economic, Finance and Banking, 2024)
The study aimed to find out a comparison of the influence of systematic risk on 11 sectoral stock returns in the time of the Russian-Ukrainian war and the Chinese property crisis. This study uses quantitative research methods with linear regression analysis tools using dummy variables. The data used in this study are secondary data in the form of time series with weekly time periods from 2021 to 2023. The study found that systematic risk values during the Russian-Ukrainian war and the Chinese property crisis were lower than in normal times. In wartime systematic risk had a significant impact only on the stock returns of the primary consumer goods sector. Meanwhile, during the Chinese property crisis systematic risk did not have a significant effect on all sectoral stock returns. In addition, in normal times systematic risks do not have a significant effect on the return of shares of the technology sector as well as property and real estate.